Using nylon Zipper ring in a community in the Peruvian Andes - Doanyre, José (2015)
An assessment of part of a family planning program is presented in a social environment characterized by high fertility, low contraceptive use and knowledge and great interest in information and practice of family planning methods. Accidental pregnancy rates and subsequent expulsions are similar to those found in urban environments and sea level. By contrast, first expulsions rates are higher than those established for suburban and metropolitan populations sea level, so it could be considered an effect of biological, possibly related to altitude conditions. The application of IUDs appears to face a number of problems arising from the socio-cultural status of the population. Although theoretically would be the most useful means of contraception in Cerro de Pasco, its use is affected by the limited knowledge of patients on the characteristics of the method, which makes it sensitive to the attitudes of mistrust generated by negative rumors. Not knowing accurately the results of studies with other methods in the same type of society is not possible to compare our retention rates. However, the parallel program of oral contraceptives have similar trends, in our experience. It could anticipate that although both methods have similar retention rates, the initial acceptance of the IUD is larger, having in this respect, an advantage. Our limited data on the use of injectable prevents a proper comparison. While the acceptability of a program of this nature is very high, since considerable demand occurs, it is necessary to maintain a high level of information activities, education and motivation, which should be permanent and mostly single type.